Influence of Transformational Leadership and Organizational Support on Employee Performance, with Employee Engagement as a Mediating Variabel - Aisyah Nur Rahmadini; Ryan Basith Fasih Khan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to determine the effect of transformational leadership and organizational support on employee performance, which is mediated by employee involvement in the educational staff of Maulana Malik Ibrahim State Islamic University Malang. research methods using quantitative methods. The data used in the study are primary data and secondary data. Sampling technique using purposive sampling. The sample studied in this study were 100 respondents who were employees of the Public Service Agency of UIN Malang. Based on the hypothesis testing conducted, it can be concluded that transformational leadership has a positive and significant impact on employee performance. In addition, transformational leadership also has a positive and significant effect on employee engagement. Organizational support, although it has an insignificant negative effect on employee performance, has a positive and significant impact on employee engagement. Employee engagement itself has a positive and significant influence on employee performance. As a mediator, employee engagement strengthens the positive and significant relationship between transformational leadership and organizational support with employee performance in the educational staff of UIN Malang.